Surgical Stress Increases Circulating Low-Density Neutrophils Which May Promote Tumor Recurrence - Kumagai, Yuko; Ohzawa, Hideyuki; Miyato, Hideyo; Horie, Hisanaga; Hosoya, Yoshinori; Lefor, Alan Kawarai; Sata, Naohiro; Kitayama, Joji (The Journal of surgical research, 2020)
Low-density neutrophils (LDN) have been shown to be increased in peripheral blood in patients with various diseases and closely related to immune-mediated pathology. However, the frequency and function of LDN in circulating blood of the patients following abdominal surgery have not been well understood. LDN were determined by CD66b(+) cells, which were copurified with mononuclear cells by density gradient preparations of peripheral blood of surgical patients. The effects of the purified LDN on T cell proliferation and tumor cell lysis were examined in vitro. Neutrophil extracellular traps (NETs) production was examined by extracellular nuclear staining. The number of LDN with an immature phenotype is markedly increased in peripheral blood samples in patients after abdominal surgery. The frequency of LDN correlated positively with operative time and intraoperative blood loss. The purified LDN significantly suppressed the proliferation of autologous T cells stimulated with anti-CD3 mAb coated on plate and partially inhibited the cytotoxicity of lymphocytes activated with recombinant interleukin-2 against a human gastric cancer cell, OCUM-1. The LDN also produced NETs after short-term culture in vitro, which efficiently trap many OCUM-1. These results suggest that surgical stress recruits immunosuppressive LDN in the circulation in the early postoperative period. The LDN may support the lodging of circulating tumor cells via NETs formation and inhibit T cell–mediated antitumor response in target organs, which may promote postoperative cancer metastases. Functional blockade of LDN might be an effective strategy to reduce tumor recurrence after abdominal surgery.